2020
DOI: 10.1101/2020.01.14.905927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theoretical and empirical quantification of the accuracy of polygenic scores in ancestry divergent populations

Abstract: Polygenic scores (PGS) have been widely used to predict complex traits and risk of diseases using variants identified from genome-wide association studies (GWASs). To date, most GWASs have been conducted in populations of European ancestry, which limits the use of GWAS-derived PGS in non-European populations. Here, we develop a new theory to predict the relative accuracy (RA, relative to the accuracy in populations of the same ancestry as the discovery population) of PGS across ancestries. We used simulations … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 49 publications
3
42
0
Order By: Relevance
“…Our results are broadly consistent with a recent estimate that LD and allele frequencies together explain up to 70% of the loss of accuracy in prediction between Europeans and Africans 44 , as well as empirical estimates that the trans-ancestry correlation in effect sizes for height is less than 1 (∼71-78%) 44,45 and therefore that the marginal effect sizes at PRS SNPs are systematically different across ancestries. We interpret this as evidence that cis -epistasis or allelic heterogeneity–which mimics epistasis 46 –contribute to these differences.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are broadly consistent with a recent estimate that LD and allele frequencies together explain up to 70% of the loss of accuracy in prediction between Europeans and Africans 44 , as well as empirical estimates that the trans-ancestry correlation in effect sizes for height is less than 1 (∼71-78%) 44,45 and therefore that the marginal effect sizes at PRS SNPs are systematically different across ancestries. We interpret this as evidence that cis -epistasis or allelic heterogeneity–which mimics epistasis 46 –contribute to these differences.…”
Section: Discussionsupporting
confidence: 91%
“…The accuracy reduction observed in the present study is largely consistent with previous studies where the European weights incurred an approximately 2.0-fold accuracy reduction for predicting East Asians as compared to predicting Europeans for anthropometric and blood-panel traits 77 as well as for BMI and height. 78 Overall, we believe DBSLMM strikes an appealing balance between computational tractability and prediction accuracy for PGS applications.…”
Section: Discussionmentioning
confidence: 92%
“…Polygenic risk scores (PRSs), which combine information across thousands of common genetic variants in the human genome, can be added to the ASCVD-PCE tool, but previous studies have reported variable predictive performance [5][6][7][8] . Additionally, these studies focused primarily on individuals with European ancestries, but it is known that the predictive accuracy of a PRS tends to attenuate in individuals with non-European ancestries [9][10][11] . We therefore undertook a clinical validation study of a new 10-year ASCVD risk prediction tool (ASCVD-IRT) that integrates a PRS for…”
Section: Introductionmentioning
confidence: 99%